Mechanical Performance of a Cascaded V-Shaped Electrothermal Actuator. (5th November 2013) - Shen, Xuejin; Chen, Xiangyu
The function and performance of MEMS are affected by the output ability of the displacement and force of microactuators. The lateral deflection of cascaded V-shaped electrothermal actuators is modelled as a triple, statically indeterminate problem. An iteration algorithm is set up to calculate the output displacement and typical forces in anchors. The calculated results of this model agree well with our own simulation results as well as with the experimental and calculated results in the literature, and we conclude that the model is credible. The paper also discusses the effects of the structure parameters and temperature increments on the displacement production ability. Clear differences were found between single and cascaded V-shaped electrothermal actuators. For the former, the maximum deflection takes place in a 0.04 rad beam angle, while for the latter the beam angle is 0.19 rad. For both types of actuators, the deflection is unrelated to the beam thickness. The displacement of the cascaded V-shaped electrothermal actuator is proportional to the temperature increment and beam length, but is inversely proportional to the beam width. Experiments on the output ability of cascaded V-shaped electrothermal actuators validated the calculated and simulation results.